Meta-Analysis: The Effect of Early Breastfeeding Initiation on Hypothermia and Diarrhea in Infants - Hidayah, Fristyaningrum; Retno, Yulia Lanti; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2021)
Background: Early initiation of breastfeeding is the process of letting the baby instinctively breastfeed within the first hour after birth, along with skin-to-skin contact between the baby and the mother's skin which can prevent hypothermia in the baby. This study aims to analyze the relationship between early initiation of breastfeeding and the incidence of hypothermia in infants. Subjects and Method: This is a systematic review and meta-analysis study. Population= Infants aged 0-59 months, Intervention= early initiation of breastfeeding, Comparison= no early initiation of breastfeeding, Outcomes= incidence of hypothermia and diarrhea. Article searched through journal databases include: PubMed, Science Direct, Google Scholar, research gate, and Springerlink. The keywords used are breastfeeding" OR "early initiation of breastfeeding" OR "initiation breastfeeding" AND newborn OR neonatal OR neonate OR infant OR children OR child AND hypothermia OR “low body temperature” OR “low temperature” OR thermoregulation OR “body temperature regulation "AND diarrhea OR diarrhea. Articles were selected with the help of PRISMA flow diagrams. Inclusion criteria included full-text articles with cross-sectional studies, multivariate analysis results in the form of AOR values and published in English from 2011-2021. Eligible articles were analyzed using Revman 5.3 application. Results: Sixteen articles from Ethiopia, Vietnam, Bangladesh, Pakistan, Tanzania, and India were included in the meta-analysis. Meta-analysis in 7 cross-sectional studies showed that early initiation of breastfeeding was able to reduce the risk of hypothermia in infants (aOR= 0.32; 95% CI= 0.21 to 0.48; p<0.001). Meta-analysis in 9 cross-sectional studies showed that early initiation of breastfeeding was able to reduce the risk of diarrhea in infants (aOR = 0.81; 95% CI = 0.76 to 0.86; p<0.001). Conclusion: Early initiation of breastfeeding reduced the risk of hypothermia and diarrhea in infants. Researchers recommend implementing early initiation of breastfeeding in the first hour of birth to prevent the risk of hypothermia and diarrhea in infants.